Molecular detection and genotypic characterization of Toxoplasma gondii in wild waterfowls in Jilin Province, Northeastern China. Issue 6 (December 2015) - Zhang, Fu-Kai; Wang, Hai-Jun; Qin, Si-Yuan; Wang, Ze-Dong; Lou, Zhi-Long; Zhu, Xing-Quan; Liu, Quan
Abstract Toxoplasma gondii can infect almost warm-blooded animals, including humans. Limited information about T. gondii infection in wild waterfowls is available in China. The present study was conducted to determine prevalence and genotype T. gondii infection in 11 wild waterfowl species in Jilin Province, northeastern China. A total of 249 wild waterfowls were sampled between April and July 2013 from Jilin Province, and the tissue samples were collected for the detection of T. gondii by a semi-nested PCR targeting the B1 gene. The positive samples were genotyped at 11 genetic markers (SAG1, 5′- and 3′-SAG2, alternative SAG2, SAG3, BTUB, GRA6, L358, PK1, c22-8, c29-2, and Apico) using multilocus polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) technology. The overall prevalence of T. gondii in the wild waterfowls was 7.2% (18/249, 95% confidence interval [CI] 4.0–10.4), with the highest prevalence (22.0%, 95% CI 10.5–33.5) in Anas formosa, followed by Anas platyrhynchos (20.0%, 95% CI 6.0–44.0), Falcated teal (12.5%, 95% CI 0.0–35.4), and Fulica atra (4.0%, 95% CI 0.0–11.7). Of 18 positive samples, only 2 samples (TgWfjl1 and TgWfjl2) were genotyped completely, and one genotype, namely ToxoDB #9, was revealed. The result of this survey has implications for better understanding of the genetic diversity of T. gondii in China. This is the first report of prevalence and genotypic characterization of T. gondii in wild waterfowls in northeastern China.